Competitive Advantage, Entrepreneurial Orientation, Knowledge Sharing, and SMEs’ Performance: Mediation-Moderation Analysis - Kadarusman, Kadarusman; Siti Rosyafah (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
The article investigates the impact of knowledge sharing on company performance with a competitive advantage as a mediating variable and entrepreneurial orientation as a moderating variable. This research uses an RBV theory to determine company performance. Knowledge sharing behavior and entrepreneurial organizations can increase competitive advantage and performance. PLS-SEM technique is employed to analyze the data from 126 Small and Medium Enterprises in the food and beverage entrepreneurs in East Java. This research indicates that knowledge sharing has a favorable and substantial influence on competitive advantage and firm performance. Knowledge sharing positively and significantly affects competitive advantage and performance directly and indirectly. Entrepreneurial orientation does not serve as a moderator.